Neural target selection as a marker of real‐world familiarity during search for perceptually distinct objects. (9th December 2020) - Ferguson, Leah; Ahmed, Claire; Dang, Christine; Wu, Rachel
Abstract: Prior studies have shown that behavioral performance is better when detecting specific familiar items based on real‐world experience (e.g., an own‐age face, a specific bird for bird experts), compared to less familiar items (e.g., an other‐age face). These biases emerge from exposure to and interactions with initially less familiar items, which allow for better discrimination and search (e.g., finding an other‐age face in a crowd). However, many broad categories in the natural environment (e.g., vintage objects, exotic fruit) contain perceptually distinct items that people can accurately search for individually, even if the objects are not as familiar. How might real‐world familiarity impact search in these cases? Recent studies suggest that the N2pc event‐related potential (ERP, neural marker of target selection) may be more sensitive than behavioral performance in reflecting prior knowledge, and perhaps familiarity, during visual search. In two experiments, the present study investigated the behavioral effects (Experiment 1) and N2pc effects (Experiment 2) of searching for distinct familiar (modern) versus less familiar (vintage) objects in younger adults. Experiment 1 also included a sample of older adults, who were familiar with both types of objects. Overall, the behavioral results did not reveal robust differences in searching for modern versus vintage objects. However, the N2pc in younger adults was present when searching for modern objects, but not for vintage objects. The N2pc results suggest that this neural marker may be more sensitive than behavioral measures in reflecting familiarity from real‐world experiences with object categories.